Carvajal, S.A. : building on a century of business growth and family values - Lansberg, Ivan, 1954- (SAGE knowledge. Cases., 2016)
This case presents the history and recent governance challenges of Carvajal, S.A., a Colombia-based, family-owned, billion-dollar-plus holding company that had offered printing-related (e.g., Yellow Pages, notebooks) and other products and services across and beyond South America for more than a century. Specifically, the case details the company's state of affairs in early 2011, a time by which Carvajal's flagship businesses had matured rapidly with the emergence of digital technology and diminished demand for paper/print-based products. Though profits and growth remained positive, Carvajal's leaders knew that upholding the business's legacy of returns, dividends for all family members, and extensive philanthropy would take significant strategy and execution.